Thermal Stability of Schottky Contacts and Rearrangement of Defects in β‐Ga2O3 Crystals - Palvan Seyidov; Joel B. Varley; Ymir Kalmann Frodason; Detlef Klimm; Lasse Vines; Zbigniew Galazka; Ta‐Shun Chou; Andreas Popp; Klaus Irmscher; Andreas Fiedler (Advanced Electronic Materials)
Abstract The thermal stability of different Schottky contacts (Au, Pt, and Ni) on (100) β‐Ga2O3 single crystals grown by the Czochralski method is investigated. Besides the examination of the Schottky barrier parameters, contact‐dependent defect levels are investigated by deep‐level transient spectroscopy (DLTS) in a 100–650 K (ramp‐up) and 650–100 K (ramp‐down) temperature cycle. Several defect levels are detected below the conduction band minimum at 0.41, 0.60, 0.77, 0.96, and 1.17 eV. In the temperature ramp‐down DLTS, the 1.17 eV level disappears, and the 0.60 eV level appears for all Schottky contacts. DFT calculations suggest that rearrangement and dissociation of a single hydrogen from a doubly‐hydrogenated Ga─O divacancy complex occurs during the temperature sweep under bias. The trap level at 0.96 eV only appears after the thermal load for the Ni contact, in contrast to Au and Pt, where it is present without a thermal budget. Temperature‐dependent leakage current (at −4 V) measurements indicate oxidation of Ni, and further thermodynamic analysis suggests alloying of Au‐Ga atoms at the Au/β‐Ga2O3 interface. These studies provide insight into the behavior induced by these common Schottky contacts and the alteration associated with temperature cycling.